Da "sagrada finalidade" aos ombros esmagados de uma classe: representações impressas sobre a profissão docente a partir da capital cearense nos anos 1940 - Silva, Manuelle Araújo da (2022)
This research has as its object of study the representations of the teaching career, with its tensions and sinuosities, from the perspective of the capital of Ceará, Fortaleza, in the 1940s, mainly in four documentary typologies: 1) Periodicals: especially the column entitled Teaching and Education written by Professor Coelho Sampaio, which is a section of the daily morning Gazeta de Notícias, as well as other newspapers in the capital of Ceará at the same time, the Revista Brasileira de Estudos Pedagógicos (RBEP) and the Almanaque do Ceará; 2) Autobiographical: which consists of Professor Coelho Sampaio's short autobiography; 3) Official: used in the examination of educational reforms and legislation; 4) Didactic literature: more specifically booklets and reading books that circulated at the time. The time frame of the research is guided by the period of circulation of the Teaching and Education column, published between the years 1944 and 1950, totaling up approximately 87 journalistic texts. It is a documentary qualitative research, guided by the intricacies of the New Cultural History. Regarding the methodological aspects, we focused on the guiding premise proposed by Jaques Revel and his concept of Scale Games (Jogos de Escala). That methodological approach allows the use of multiple angles of analysis present in this investigation. Those angles of analysis range from a journalistic column in the capital of Ceará to the overall Brazilian conjuncture, which also allow the analysis to be done in the opposite way, from macro to micro. This alternation of scales makes it possible to investigate the tension established between two types of concepts related to the teaching career in the 1940s: one of them is more linked to the ideas of career, method, training preparation and union rights; different from the other type which is more connected with the focus of mission, selflessness, vocation, and with the apostolic imagination as a whole. This study provides an opportunity to understand that, in the space-time context analyzed in this paper, among the multiple ways of representing teaching, the concepts arising from the missionary/religious ideal and the concepts linked to the career/method, despite suggesting paradoxical interpretations, often times co-existed in pedagogical discourses. Furthermore, it is concluded that the Teaching and Education column was established as a prominent space for speech and cultural mediation, four 4 reasons: the marked circulation of the newspaper Gazeta de Notícias; the scope of its readership that transcended those who practiced the teaching profession; the long period of publication of that column; the foundation/adherence to the Cearense Association of Pedagogical Studies (ACEP), which started from the initiative of Coelho Sampaio in his column and from the replicas of professional peers to their printed educational positions.